2017
DOI: 10.1186/s12879-017-2594-3
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazinamide resistance-conferring mutations in pncA and the transmission of multidrug resistant TB in Georgia

Abstract: BackgroundThe ongoing epidemic of multidrug-resistant tuberculosis (MDR-TB) in Georgia highlights the need for more effective control strategies. A new regimen to treat MDR-TB that includes pyrazinamide (PZA) is currently being evaluated and PZA resistance status will largely influence the success of current and future treatment strategies. PZA susceptibility testing was not routinely performed at the National Reference Laboratory (NRL) in Tbilisi between 2010 and September 2015. We here provide a first insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Using our composite reference standard (MGIT, classic Wayne test, and pncA sequencing), we found that around half of the selected MDR-TB strains were PZA resistant (30/57 samples [52.6%]), but few of the selected pansusceptible strains were PZA resistant (4/101 samples [4.0%]). These findings are in agreement with rates reported by other studies (3, 6, 20).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Using our composite reference standard (MGIT, classic Wayne test, and pncA sequencing), we found that around half of the selected MDR-TB strains were PZA resistant (30/57 samples [52.6%]), but few of the selected pansusceptible strains were PZA resistant (4/101 samples [4.0%]). These findings are in agreement with rates reported by other studies (3, 6, 20).…”
Section: Discussionsupporting
confidence: 94%
“…All sputum samples selected for this study were positive for TB according to the MODS assay. Given that MDR-TB isolates have a 50% chance of also being resistant to PZA (3, 14, 29), in order to select a high number of PZA-resistant sputum samples for evaluation, we selected approximately 50% of specimens that were MDR and monoresistant to isoniazid or rifampin and 50% of non-MDR specimens. Data concerning patient age, sex, and TB treatment were collected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PZA, a synthetic derivative of nicotinamide, is used as a first-line drug, and PZA resistance is attributed to mutations in pncA encoding a pyrazinamidase [ 27 ]. However, these resistance-conferring mutations are variable and widely dispersed [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…PZA is the only drug with different activity in vivo and in vitro [17]. Its importance is based on its in vivo sterilizing effect that permits killing of persistent bacilli [18]. PZA is frequently used in both first-and second-line treatment regimens [19][20][21].…”
Section: Introductionmentioning
confidence: 99%